2021
DOI: 10.3390/app11020871
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Microalgae and Cyanobacteria in the Improvement of Agricultural Practices: A Review on Their Biofertilising, Biostimulating and Biopesticide Roles

Abstract: The increase in worldwide population observed in the last decades has contributed to an increased demand for food supplies, which can only be attained through an improvement in agricultural productivities. Moreover, agricultural practices should become more sustainable, as the use of chemically-based fertilisers, pesticides and growth stimulants can pose serious environmental problems and lead to the scarcity of finite resources, such as phosphorus and potassium, thus increasing the fertilisers’ costs. One pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(102 citation statements)
references
References 129 publications
(247 reference statements)
1
64
0
1
Order By: Relevance
“…They are categorized into three groups: microbial biopesticides, biochemical biopesticides, and PIPs (Leahy et al, 2014;Liu et al, 2019;Ram and Singh, 2021). Bacillus thuringiensis (Bt) control 90% of the microbial biopesticide market; however, Beauveria bassiana, Baculovirus, Steinernema, Nosema, and Chlorella have also demonstrated significant roles (Steinkraus and Tugwell, 1997;Abu-Dieyeh and Watson, 2007;Radwan et al, 2018;Gonçalves, 2021). Biochemical biopesticides are compounds (or exact synthetic analog) of natural origin possessing active ingredients that control pest by mechanisms that are nontoxic to the target pest, the environment and humans (Kumar, 2012;Reddy and Chowdary, 2021).…”
Section: Definition and Categories Of Biopesticidesmentioning
confidence: 99%
“…They are categorized into three groups: microbial biopesticides, biochemical biopesticides, and PIPs (Leahy et al, 2014;Liu et al, 2019;Ram and Singh, 2021). Bacillus thuringiensis (Bt) control 90% of the microbial biopesticide market; however, Beauveria bassiana, Baculovirus, Steinernema, Nosema, and Chlorella have also demonstrated significant roles (Steinkraus and Tugwell, 1997;Abu-Dieyeh and Watson, 2007;Radwan et al, 2018;Gonçalves, 2021). Biochemical biopesticides are compounds (or exact synthetic analog) of natural origin possessing active ingredients that control pest by mechanisms that are nontoxic to the target pest, the environment and humans (Kumar, 2012;Reddy and Chowdary, 2021).…”
Section: Definition and Categories Of Biopesticidesmentioning
confidence: 99%
“…Abiotic stresses adversely affect growth, productivity and trigger a series of morphological, physiological, biochemical and molecular changes in plants. A direct link between seaweed/microalgae and these parameters can be done, ensuring real interest in the use of these bioproducts in order to stabilize potential financial losses (Gonçalves, 2021). The effects of germination parameters ( percentage index, mean time) and growth parameters (shoot and root length) of mung bean (Vigna radiata) treated with acid seaweed liquid of Ulva latucta extracts at 0.2% were evaluated by Castellanos-Barriga et al (2017).…”
Section: Yield and Nutritional Qualitymentioning
confidence: 99%
“…Their ethanol extract of Sargassum wightii presented larvicidal activity against Aedes aegypti (dengue and Zika virus vector). Another insect problem, the Asian citrus psyllid Diaphorina citri, has been controlled by repellent and insecticidal effects of ethanolic extracts obtained from Caulerpa sertularioides, Laurencia johnstonii and Sargassum horridum seaweeds (González-Castro et al, 2019). A recent example of success against nematodes is the use of three microalgae (Scenedesmus obliquus, Chlorella vulgaris and Anabaena oryzae), alone or in combination, to control the root-knot nematode Meloidogyne incognita.…”
Section: Inhibition Of Other Plant Pestsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microalgae have become one of the alternative raw materials for biofuel production due to their high carbohydrate and fat content, fast growth rate, and strong resistance to the environment [2,3]. Reports have shown that the photosynthetic productivity of microalgae is several folds higher than that of higher plants, which also increases the fatty acid synthesis in certain microalgae [4,5]. Furthermore, microalgae can also resolve the problem of land competition between traditional oil crops and food crops.…”
Section: Introductionmentioning
confidence: 99%